Basic, applied and experimental knowledge and productivity: Further evidence - Kul B. Luintel; Mosahid Khan (Cardiff University, Cardiff Business School, 2011)
Analyzing a novel dataset we find significantly positive effects of basic, and applied and experimental knowledge stocks on domestic output and productivity for a panel of 10 OECD countries. This letter updates the work of, among others, Mansfield (1980), Griliches (1986) and Adams (1990), at an international setting.
Keywords: F12; F2; O3; 330; Basic and Applied Research; TFP; Panel Co-integration; Wissen; Humankapital; Produktivität; OECD-Staaten